OPINI MAHASISWA MENGENAI ISU PEMINDAHAN LOKASI PELAKSANAAN HUKUM CAMBUK KE PENJARA (Studi Kasus Pada Mahasiswa Prodi Hukum FISIP UTU) - rena juliana (SOURCE : Jurnal Ilmu Komunikasi, 2018)
This research aims to analyze how students of Law Major of Social and Political Sciences Faculty ofTeuku Umar University responded to the issue of transferring the location of the execution of the caningto prison. Spiral of silence theory is the underlying theory of this research. The method used in thisresearch is quantitative descriptive method by distributing questionnaires to 20 students. From the resultsof the research found that the students did not agree with the government plan to move the location of theexecution of the caning to prison. It is considered that such a punishment will not make the defendantsdeterrent because the effect of shame does not exist. The defendant will not be punished by the public fornot being shown publicly. The students also considered that the prohibition to take pictures andrecordings when the process of application of caning law should not be prohibited. In addition thestudents considered that the implementation of caning law in the mosque will not cause a sense of thephobia of investors to instill their shares in Aceh and the implementation of caning law in the mosquedoes not violate human rights. The students alleged the transfer of location of the canning law full ofpolitical interests so it is feared that the ruling parties in violation of the Shariah will not receive thecaning punishment because of their power.Keyword: Opinion, students of Law Major, Caning1. PENDAHULUAN